(untitled) (Journal of Oriental Studies, 2019)
This article discusses the commentary on the compulsory execution of the istita’a for a Muslim before pilgrimage. The article focuses on two issues. The first is to define the importance and role of pilgrimage in Islam. The second is an analysis of the differences in the understanding of istita’a when making a pilgrimage in accordance with the four legal madhhabs (Shafi’i, Maliki, Hanbali and Hanafi). In preparing this article, data related to the topic were collected, analyzed, and a substantial comparative analysis was carried out.. The results of the study show that istita’a means a person’s ability to perform Islamic practices in accordance with their capabilities. In addition, the study proved that different opinions are formulated between the scientists of the four madhhabs regarding the requirements of istita’a for pilgrimage. The article also discussed in detail the concept of istita’a in the pilgrimage according to the Hanafi madhhab. Key words: pilgrimage in Islam, the concept of istita’a, the madhhabs of Shafi’i, Maliki, Hanbali and Hanafi.